PENGARUH KONSENTRASI KEPEMILIKAN, TRANSAKSI DENGAN PIHAK BERELASI DAN MANAJEMEN LABA TERHADAP DAYA INFORMASI AKUNTANSI - ROHMATULLAILY, NURUL (Jurnal Akuntansi AKUNESA, 2019)
The purpose of this research is to analyze the effect of Ownership Concentration, Related Party Transactions and Earnings Management to Informativeness of Accounting. This research is quantitative research using secondary data in the form of financial report from each company. Samples in this research are 252 financial statements from all companies listed on Indonesia Stock Exchange (BEI) in 2014 and 2015 which were selected based on the stratified sampling method. The analysis technique used in this research is multiple linear regression analysis using SPSS 22. The results show that ownership concentration variables, related party transactions and earnings management do not have an effect on the informativeness of accounting. The result of the coefficient determination is 0.000 which show that the large percentage informativeness of accounting cannot explain the independent variables, so the informativeness of accounting can be explain with the other variables.Keyword: Ownership Concentration, Related Party Transactions, Earning Management, Informativeness of Accounting